The Analysis of Figurative Language Found in English Lyrics of Song “Easy on Me” By Adele Laurie - Yulianti; Nur Azmi Rohimajaya; Riandi (Innovations in Multidisciplinary Education Journal, 2024)
The Aims of the research Paper are: To Find out the Types of Figurative Language are used in English Lyric of Song’s, Meaning of this Figurative Language in English Lyric of Song’s and To Find out the Most Dominant Figurative Language in English Lyric of Song’s. in this Research, the researcher used the Qualitative Research since the Data are in the Form of Written or Oral Words the Techniques of Collecting Data, the Collected From the Song’s Entitled of  “Easy on Me” By Adele Laurie. and the researcher did 8 Steps to the Techniques of Analysis Data, Follows: Listening the Songs, Reading the Song Lyrics, Underlining the Word Which Related in Figurative Language, Identifying, Classifies Certain Lyrics, Reanalyzed the Song Lyrics, Coding, and the Last the researcher make a Table and a Pie Chart. The Finding of the Research, The researcher Found Seventeen the Figurative Language in English Lyrics of Song’s are: Alliteration, Hyperbola, Idiom, Irony Litotes, Metaphor, Metonimia, Onomatopoeia, Oxymoron, Personification, Repetition and Simile . The Most Dominant Figurative Language which are used in the Song Lyrics is Repetition Found Three Song Lyric.